Significant improvement in superconducting properties of in situ powder-in-tube MgB2 wires through anthracene doping and heat treatment optimization. (21st August 2019) - Li, Chunyan; Suo, Hongli; Ma, Lin; Yang, Liangqun; Maeda, Minoru; Patel, Dipak; Matsumoto, Akiyoshi; Kumakura, Hiroaki
Abstract: High-performance MgB2 single-filament powder in tube wires were obtained through anthracene doping and heat treatment optimization. The heat treatment condition which optimizes J c depends on the amount of anthracene doping in the wire. The higher the doping amount, the higher the sintering temperature or the longer the holding time. The combined effects of doping amount and sintering condition on the microstructural and superconducting properties of MgB2 wires after optimized heat treatment have been systematically investigated. The actual level of C substitution in Mg(B1− x C x )2 was increased with the doping amount of anthracene. The obvious improvements in the irreversibility field ( H irr ) and critical current density ( J c ) have been observed in anthracene doped MgB2 wires. However, the highest critical current density ( J c ) of 1.82 × 10 4 A cm −2 at 4.2 K/10 T was obtained by 3.75 at%C (anthracene) doped wire which was heat-treated at 650 °C for 2 h. These results suggest that anthracene is an effective carbon source and that heat treatment optimization is quite necessary for obtaining high J c performance.